Problemy współczesnych badań empirycznych w Polsce = Issues in contemporary empirical research in Poland - Lisowski, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the first issue of the methodological journal "ASP", initially published in 1995, the authors H. Domański, Z. Sawiński, F. Sztabiński and P.B. Sztabiński outlined probable directions of the development of sociological research in Poland. The present article aims at juxtaposing the predictions with 15 years of research practice.
Keywords: badania socjologiczne; badania empiryczne; badania marketingowe